Electrical properties, characterization, and preparation of composite materials containing a polymethacrylate with ?-naphthyl side group and nanographene fillers - Abubakar, Abdullahi Musa; Biryan, Fatih; Demirelli, Kadir (Sage Publications Ltd, 2021)
2-(Naphthalene-1-yl oxy)-2-oxoethyl methacrylate (NOEMA) was synthesized from reaction of naphthalene-1-yl 2-chloroacetate and sodium methacrylate and its homopolymer was prepared by free-radical polymerization method at 60 degrees C. The glass transition temperature of pure poly(NOEMA) was estimated as 102 degrees C by differential scanning calorimetry technique, whereas that of poly(NOEMA) containing 10 wt% nanographene was 83 degrees C. While pure poly(NOEMA) from thermogravimetric analysis measurements was indicating a decomposition at 290 degrees C, poly(NOEMA) composite containing 10 wt% nanographene showed thermal decomposition temperature at 261 degrees C. Semiconducting composites of poly(NOEMA) have been prepared by adding nanographene particles to poly(NOEMA) for preparing nanocomposites with different weight percentages (2, 3, 4, 5, and 10 wt%). The dielectric constant, SMALL ELEMENT OF ', and dielectric loss factor, SMALL ELEMENT OF '', of pure poly(NOEMA) were 3.66 and 0.052, respectively, whereas those of poly(NOEMA) containing 10 wt% nanographene were 186 and 210,152, respectively. Alternating current (AC) conductivity of pure poly(NOEMA) was 2.03 x 10(-9) S cm(-1), whereas that of poly(NOEMA) containing 10 wt% nanographene was 0.00134 S cm(-1). AC conductivity mechanism of poly(NOEMA)/10 wt% nanographene composite indicated the correlated barrier hopping model. Activation energy values of poly(NOEMA)/x wt% nanographene composites was estimated to be between 4.783 eV and 0.209 eV. The polymer composite/p-Si thin-film heterojunction diode properties have been investigated from current-voltage at room temperature. The electrical parameters of the prepared diodes such as ideality factor (n), the barrier height (BH; phi(b)), rectification ratio, and reverse saturation current (I-o) were investigated at dark and room temperature. The ideality factor (n) value of the Al/poly(NOEMA)/x wt% nanographene/p-Si/Al diode for dark was found to be between 5.147 and 7.504, respectively. The BH (phi(b)) value of the Al/poly(NOEMA)/x wt% nanographene/p-Si/Al diode at dark was found to be between 0.228 and 0.64.
Keywords: Electrical measurements; thermal behavior; synthesis; diode properties